2013
DOI: 10.1179/1754762812y.0000000009
|View full text |Cite
|
Sign up to set email alerts
|

Measuring listening effort expended by adolescents and young adults with unilateral or bilateral cochlear implants or normal hearing

Abstract: The similar amount of listening effort expended by the two groups indicated that a higher signal-to-noise ratio overcame limitations in the auditory information received or processed by the participants with implants. This study is the first to objectively compare listening effort using two versus one cochlear implant. The results provide objective evidence that reduced listening effort is a benefit that some individuals gain from bilateral cochlear implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
3
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 31 publications
5
68
3
5
Order By: Relevance
“…Stokes (2010) suggests that words from dense neighborhoods tend to be acquired earlier than those from sparse neighborhoods because adults tend to hyper-articulate words from dense neighborhoods to avoid confusions, which consequently makes words from dense neighborhoods more salient. Due to the bilateral advantage on speech perception (Grieco-Calub & Litovsky, 2012; Hughes & Galvin, 2013; Lovett, Kitterick, Hewitt, & Summerfield, 2010), children with bilateral CIs may be able to benefit from these hyper-articulated patterns more than children with unilateral CIs do.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stokes (2010) suggests that words from dense neighborhoods tend to be acquired earlier than those from sparse neighborhoods because adults tend to hyper-articulate words from dense neighborhoods to avoid confusions, which consequently makes words from dense neighborhoods more salient. Due to the bilateral advantage on speech perception (Grieco-Calub & Litovsky, 2012; Hughes & Galvin, 2013; Lovett, Kitterick, Hewitt, & Summerfield, 2010), children with bilateral CIs may be able to benefit from these hyper-articulated patterns more than children with unilateral CIs do.…”
Section: Discussionmentioning
confidence: 99%
“…If binaural input enhances perception of acoustic information (Grieco-Calub & Litovsky, 2012; Lovett et al, 2010), children with bilateral CIs may process the sound sequence of words in greater detail and thus demonstrate stronger sensitivity to word statistics than children with unilateral CIs. Moreover, binaural processing may reduce listening effort (Hughes & Galvin, 2013), which allows children with bilateral CIs to allocate more attention and/or other cognitive resources to the process of lexical acquisition (Houston et al, 2003; Just & Carpenter, 1992). In fact, it has been suggested that early auditory experience can affect the development of general cognitive processes that are not even specific to audition or spoken language (Conway, Pisoni, & Kronenberger, 2009; Houston et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there are only a handful of published studies on listening effort with teen-age or pediatric participants (e.g., Choi et al 2008;Howard et al 2010;Hughes & Galvin 2013;Gustafson et al 2014). Moreover, since children experience significant linguistic and cognitive maturation during their elementary school years (e.g., Cartwright 2002;Piaget & Inhelder 2008), the same behavioural paradigm may yield different patterns of results between children and adults.…”
Section: School-age Childrenmentioning
confidence: 99%
“…When one task becomes more difficult, in this case trying to understand speech that is both degraded and mixed with competing noise, additional effort is necessary to maintain performance. Neurocognitive measures have been employed recently to assess the information processing workload demands required for listening to speech in background noise for CI listeners [70,71] and normal hearing participants under CI simulation [72]. Some of these behavioral measures rely on self-report [73], speed of processing [74,75], physiological responses such as pupillometry [77], or "dual-task" methodologies to assess listening effort and mental workload [78][79].…”
Section: Speech In Noisementioning
confidence: 99%